Castle Craneycrow - McCutcheon, George Barr, 1866-1928 (Salt Lake City, UT : Project Gutenberg, 2004)
"Castle Craneycrow" by George Barr McCutcheon is a novel written in the early 20th century. The story centers around Philip Quentin, a charming and wealthy young man in New York City who finds himself embroiled in unexpected relationships that intertwine his past with intrigue and romance, particularly concerning his former love, Dorothy Garrison, now engaged to a prince. The opening of the novel introduces us to Philip Quentin's character through a series of amusing and whimsical interactions, the most notable being his encounter with a burglar named James Turkington, who comes to be known as Turk. After capturing Turk during a break-in, Quentin invites him to supper, forming an unusual bond that sees the burglar transformed into a loyal servant. As the narrative unfolds, we glimpse Quentin's adventurous spirit and his gradual entanglement in romantic tensions involving Dorothy and the enigmatic Prince Ugo. These early chapters set the stage for a blend of comedy, romance, and the complexities of class dynamics as Quentin navigates his feelings and connections against the backdrop of his charmed yet complicated life. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Charles Aldarondo and David Widger
Keywords: Love stories; Abduction -- Fiction; Americans -- Europe -- Fiction